Portland (Oregon) Domestic Violence Experiment, 1996-1997 - Jolin, Annette ([Verlag nicht ermittelbar], 2002)
As part of its organization-wide transition to community policing in 1989, the Portland Police Bureau, in collaboration with the Family Violence Intervention Steering Committee of Multnomah County, developed a plan to reduce domestic violence in Portland. The creation of a special police unit to focus exclusively on misdemeanor domestic crimes was the centerpiece of the plan. This police unit, the Domestic Violence Reduction Unit (DVRU), had two goals: to increase the sanctions for batterers and to empower victims. This study was designed to determine whether DVRU strategies led to reductions in domestic violence. Data were collected from official records on batterers (Parts 1-10), and from surveys on victims (Parts 11-12). Part 1 (Police Recorded Study Case Data) provides information on police custody reports. Part 2 (Batterer Arrest History Data) describes the arrest history during a five-year period prior to each batterer's study case arrest date. Part 3 (Charges Data for Study Case Arrests) contains charges filed by the prosecutor's office in conjunction with study case arrests. Part 4 (Jail Data) reports booking charges and jail information. Part 5 (Court Data) contains sentencing information for those offenders who had either entered a guilty plea or had been found guilty of the charges stemming from the study case arrest. Data in Part 6 (Restraining Order Data) document the existence of restraining orders, before and/or after the study case arrest date. Part 7 (Diversion Program Data) includes deferred sentencing program information for study cases. Variables in Parts 1-7 provide information on number of batterer's arrests for domestic violence and non-domestic violence crimes in the past five years, charge and disposition of the study case, booking charges, number of hours offender spent in jail, type of release, type of sentence, if restraining order was filed after case arrest, if restraining order was served or vacated, number of days offender stayed in diversion program, and type of diversion violation incurred. Part 8 (Domestic Violence Reduction Unit Treatment Data) contains 395 of the 404 study cases that were randomly assigned to the treatment condition. Variables describe the types of services DVRU provided, such as taking photographs along with victim statements, providing the victim with information on case prosecution, restraining orders, shelters, counseling, and an appointment with district attorney, helping the victim get a restraining order, serving a restraining order on the batterer, transporting the victim to a shelter, and providing the victim with a motel voucher and emergency food supply. Part 9 (Police Record Recidivism Data) includes police entries (incident or arrest) six months before and six months after the study case arrest date. Part 10 (Police Recorded Revictimization and Reoffending Data) consists of revictimization and reoffending summary counts as well as time-to-failure data. Most of the variables in Part 10 were derived from information reported in Part 9. Part 9 and Part 10 variables include whether the offense in each incident was related to domestic violence, whether victimization was done by the same batterer as in the study case arrest, type of police action against the victimization, charges of the victimization, type of premises where the crime was committed, whether the police report indicated that witnesses or children were present, whether the police report mentioned victim injury, weapon used, involvement of drugs or alcohol, whether the batterer denied abuse victim, number of days from study cases to police-recorded revictimization, and whether the recorded victimization led to the batterer's arrest. Part 11 (Wave 1 Victim Interview Data) contains data obtained through in-person interviews with victims shortly (1-2 weeks) after the case entered the study. Data in Part 12 (Wave 2 Victim Interview Data) represent victims' responses to the second wave of interviews, conducted approximately six months after the study case victimization occurred. Variables in Part 11 and Part 12 cover the victim's experience six months before the study case arrest and six months after the study case arrest. Demographic variables in both files include victim's and batterer's race and ethnicity, employment, and income, and relationship status between victim and batterer. Information on childhood experiences includes whether the victim and batterer felt emotionally cared for by parents, whether the victim and batterer witnessed violence between parents while growing up, and whether the victim and batterer were abused as children by a family member. Variables on the batterer's abusive behaviors include whether the batterer threatened to kill, swore at, pushed or grabbed, slapped, beat, or forced the victim to have sex. Information on the results of the abuse includes whether the abuse led to cuts or bruises, broken bones, burns, internal injury, or damage to eyes or ears. Information was also collected on whether alcohol or drugs were involved in the abuse events. Variables on victims' actions after the event include whether the victim saw a doctor, whether the victim talked to a minister, a family member, a friend, a mental health professional, or a district attorney, whether the victim tried to get an arrest warrant, went to a shelter to talk, and/or stayed at a shelter, whether the victim asked police to intervene, tried to get a restraining order, talked to an attorney, or undertook other actions, and whether the event led to the batterer's arrest. Variables on victim satisfaction with the police and the DVRU include whether police or the DVRU were able to calm things down, recommended going to the district attorney, informed the victim of her legal rights, recommended that the victim contact shelter or support groups, transported the victim to a hospital, and listened to the victim, whether police treated the victim with respect, and whether the victim would want police or the DVRU involved in the future if needed. Variables on the victim's emotional state include whether the victim was confident that she could keep herself safe, felt her family life was under control, and felt she was doing all she could to get help. Other variables include number of children the victim had and their ages, and whether the children had seen violence between the victim and batterer.